Person Named Entity Recognition in Balinese - Kurniadi, Kenny; ER, Ngurah Agus Sanjaya (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2021)
Named Entity Recognition (NER) is part of information extraction whose task is to classify text which is categorized into several classes such as names of people (figures), organizations, and locations. In this study, the authors propose making a NER identify the names of characters in Balinese language documents. This study will use a rule-based method (rule-based). Rules are build based on the morphological structure and linguistic meaning of Balinese names. The research conducted, that the system has an accuracy of 67.41%, precision of 83.42%, recall of 77.83%, and F-Score of 80.53%.